2016
DOI: 10.1055/s-0035-1566163
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Transfer for Esthetic Contouring of Face in Posttraumatic Nonfunctional Maxillofacial Deformities

Abstract: The transfer of autologous fat has been performed since the 1890s; however, its popularity has increased owing to better understanding of fat harvesting and processing techniques. In this article, fat grafting procedure has been used to correct posttraumatic facial deformities in 25 cases. As healing of grafted fat is unpredictable, we have used longer follow-up of 2 years. Evaluation was performed using facial photographs and MRI scans. Scientific literature describes an absorption rate ranging from 20 to 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Fat grafting first gathered prominence in the aesthetic area (24), and subsequent study showed it had a favourable complication profile compared to synthetic filler materials (25,26).…”
Section: Autologous Fat Graftingapplications and Indications Of Autolmentioning
confidence: 99%
“…Fat grafting first gathered prominence in the aesthetic area (24), and subsequent study showed it had a favourable complication profile compared to synthetic filler materials (25,26).…”
Section: Autologous Fat Graftingapplications and Indications Of Autolmentioning
confidence: 99%
“…However, its therapeutic effects are not maintained over time, because it has an absorbable micromolecular structure. Autologous structural fat transplant is traditionally used for treating facial soft tissue depressions [1-3], and in addition to improving facial structure, it notably improves skin condition.…”
Section: Introductionmentioning
confidence: 99%
“…[1–4] Several factors can cause such disease, including cleft lip, cleft palate, cancer, trauma, and automobile accident. [511] It has been reported that about 20% of the world's population have some major OMDF. [12,13] It has greatly affected the health-related quality of life in patients with OMDF.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is a very effective treatment for patients with OMDF. [2,4,5,7,8,17–23] Although a variety of studies have reported the efficacy and safety of surgery, especially for orthodontic and orthognathic treatment (OOT) for the management of OMDF, there is still inconsistent conclusion. [2,4,18–22] Thus, this study will assess the efficacy and safety of OOT for the treatment of patients with OMDF.…”
Section: Introductionmentioning
confidence: 99%